2015
DOI: 10.1016/j.pscychresns.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex, emotional decision-making and response to cognitive behavioural therapy for psychosis

Abstract: Grey matter volume (GMV) in the orbitofrontal cortex (OFC) may relate to better response to cognitive behavioural therapy for psychosis (CBTp) because of the region׳s role in emotional decision-making and cognitive flexibility. This study aimed to determine the relation between pre-therapy OFC GMV or asymmetry, emotional decision-making and CBTp responsiveness. Emotional decision-making was measured by the Iowa Gambling task (IGT). Thirty patients received CBTp+standard care (CBTp+SC; 25 completers) for 6–8 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 70 publications
4
25
1
Order By: Relevance
“…Patients with greater grey matter volume in the areas associated with a good CBTp response were perhaps relatively better at coordination of mental activity, cognitive flexibility, verbal learning, and memory, all of which can be expected to facilitate CBTp. A more recent study [31], using a region-of-interest approach and the same sample reported previously by Premkumar and colleagues [30], demonstrated an association between larger grey matter volume of the orbitofrontal cortex and symptom reduction following CBTp. This association is most likely explained by the role of orbitofrontal cortex in emotional decision-making and cognitive flexibility [73].…”
Section: Structural Mrimentioning
confidence: 56%
See 2 more Smart Citations
“…Patients with greater grey matter volume in the areas associated with a good CBTp response were perhaps relatively better at coordination of mental activity, cognitive flexibility, verbal learning, and memory, all of which can be expected to facilitate CBTp. A more recent study [31], using a region-of-interest approach and the same sample reported previously by Premkumar and colleagues [30], demonstrated an association between larger grey matter volume of the orbitofrontal cortex and symptom reduction following CBTp. This association is most likely explained by the role of orbitofrontal cortex in emotional decision-making and cognitive flexibility [73].…”
Section: Structural Mrimentioning
confidence: 56%
“…The search was run on 12th May 2017 with no time range specified for the date of publication. Our search revealed 9 papers in total [24][25][26][27][28][29][30][31][32], all published within the last 10 years (see Table 1 for greater details).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…80 There was a significant correlation between pre-treatment orbitofrontal cortex gray matter volume and positive symptom improvement (r = 0.530; p = 0.01) after a CBT protocol. The authors also found an association between rightward orbitofrontal cortex asymmetry and reduction of negative (r = 0.542; p = 0.01) and general psychopathology (r = 0.482; p = 0.02).…”
Section: Cbt For Schizophrenia and Neurobiological Findingsmentioning
confidence: 91%
“…Kumari et al (70) revealed that changes in activation in regions responsible for language processing, attention, insight and self-awareness were associated with symptom improvement. Premkumar et al (71) demonstrated that increased gray matter in the orbitofrontal cortex, a region associated with impulsivity and emotional decision making, was also associated with response to CBTp. Increases in the anterior cingulate cortex (ACC) of a metabolite associated with mitochondrial and NMDA receptor function as well as neuronal longevity known as N-acetyl aspartate (NAA) were also associated with symptom improvement after CBTp (72).…”
Section: Cognitive Behavior Therapy For Psychosismentioning
confidence: 99%